EXTERNAL CONFLICT IN “FLIPPED” MOVIE - Angraeni, Cindy; Nur, Sahril (Journal of English Literature and Linguistic Studies, 2023)
This study describes the external conflicts contained in the film "Flipped" and the types of conflicts that exist in the film. This study aims to analyze the external conflict in the film "Flipped" using Kenney's theory (1966) to analyze the types of conflict faced by the main character and Soekanto's theory (1992) to examine the factors that cause conflict and conflict resolution. The research method used in this research is descriptive qualitative. The researcher analyzes the conflicts that occur in the movie "Flipped." The results showed that there were 30 extracts found. The researcher found 3 out of 3 types of external conflict and found 2 out of 4 factors that cause conflict and 2 out of 5 conflict resolution methods. In the movie, the researcher found 3 types of external conflicts which are man versus man (13 extracts), man versus nature (2 extracts), and man versus society (3 extracts). To examine the causes and methods of conflict resolution, researchers use the theory put forward by Soekanto (1992), there are 2 causes of conflict found in the movie "Flipped". In the movie the researchers found 2 causes of conflict which are differences between individuals (4 extracts) and differences of interest (3 extracts). In addition, the researcher found 2 methods of conflict resolution, there are compromising (2 extracts) and mediation (3 extracts).